Proposal of Biomass Heat Source for Microcogeneration Unit - Durcansky, Peter; Jandacka, Jozef (Manufacturing Technology Journal, 2015)
The use of renewable energy sources in Slovakia is currently very debated issue. The main cause of this discussion is the increase of energy prices, which increasingly burden the population and companies. The use of renewable sources, including biomass, represents an important contribution to solve this problem. When new heat source is designed, several technical regulations and recommendations must be followed. The proposed device is intended to serve for combustion of biomass, in the form of wood, of pellets. The aim of this work is to describe the design process of the combustion device as the main source of thermal energy in our proposed micro-cogeneration unit.
Keywords: Biomass; combustion; microcogeneration unit